Effect of Rutin on Cytarabine-Associated Pulmonary Oedema and Oxidative Stress in Rats - BILGIN,ASLI O. (2020)
Abstract Cytarabine is effectively used in the treatment of ﻿adult acute leukemia, but it has a dose-limiting side effect of fatal pulmonary oedema because it increases the vascular permeability of the alveolar capillaries. The aim of the present study was to conduct a radiological, biochemical and histopathological investigation of the effect of rutin on cytarabine-associated pulmonary oedema in rats. Rats were treated with a combination of rutin+cytarabine by administering oral rutin at a dose of 50 mg/kg; other rat groups were orally administered the same volume of physiological saline. One hour after administration of rutin or saline, the rutin+cytarabine and cytarabine groups received an intraperitoneal injection of cytarabine (200 mg/kg). This administration procedure was repeated once a day for 14 days. Radiologically, 50% of the animals given cytarabine alone showed lung oedema, but the rutin+cytarabine group showed no oedema. The inclusion of rutin decreased the amounts of cytarabine-associated malondialdehyde, tumour necrosis factor-α, and nuclear factor-κB in the lung tissue. Rutin also inhibited the reduction of total glutathione by nitric oxide. These findings suggest that rutin may be a beneficial adjunct that can minimise the development of cytarabine-associated pulmonary oedema.